Vitamin-Containing Antioxidant Formulation Reduces Carcinogen-Induced DNA Damage through ATR/Chk1 Signaling in Bronchial Epithelial Cells In Vitro - J.P. Jose Merlin (MDPI AG, 2021)
Lung cancer has the highest mortality rate worldwide and is often diagnosed at late stages, requiring genotoxic chemotherapy with significant side effects. Cancer prevention has become a major focus, including the use of dietary and supplemental antioxidants. Thus, we investigated the ability of an antioxidant formulation (AOX1) to reduce DNA damage in human bronchial epithelial cells (BEAS-2B) with and without the combination of apple peel flavonoid fraction (AF4), or its major constituent quercetin (Q), or Q-3-O-d-glucoside (Q3G) in vitro. To model smoke-related genotoxicity, we used cigarette-smoke hydrocarbon 4-[(acetoxymethyl)nitrosamino]-1-(3-pyridyl)-1-butanone (NNKOAc) as well as methotrexate (MTX) to induce DNA damage in BEAS-2B cells. DNA fragmentation, γ-H2AX immunofluorescence, and comet assays were used as indicators of DNA damage. Pre-exposure to AOX1 alone or in combination with AF4, Q, or Q3G before challenging with NNKOAc and MTX significantly reduced intracellular reactive oxygen species (ROS) levels and DNA damage in BEAS-2B cells. Although NNKOAc-induced DNA damage activated ATM-Rad3-related (ATR) and Chk1 kinase in BEAS-2B cells, pre-exposure of the cells with tested antioxidants prior to carcinogen challenge significantly reduced their activation and levels of γ-H2AX (p ≤ 0.05). Therefore, AOX1 alone or combined with flavonoids holds promise as a chemoprotectant by reducing ROS and DNA damage to attenuate activation of ATR kinase following carcinogen exposure.